2006
DOI: 10.1089/apc.2006.20.803
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Related Knowledge, Attitudes, Perceived Benefits, and Risks of HIV Testing Among Pregnant Women in Rural Southern India

Abstract: The rising prevalence of HIV among pregnant women in rural India is of great concern. Prenatal voluntary counseling and HIV testing (VCT) is critical to prevent mother-to-child transmission of HIV (PMTCT). We surveyed 202 pregnant women attending a rural antenatal clinic in Southern India to investigate HIV-related knowledge, attitudes toward infant feeding practices, and perceived benefits and risks of HIV testing. Of the total of 202 women surveyed, 189 women (94%) had heard of HIV/AIDS and 60% of them had r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
4
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 22 publications
7
60
4
9
Order By: Relevance
“…Quantitative studies are based on samples ranging in size from 200 to 97 240 respondents from the student, general population (NACO, BSS-2006) and health staff (Mahendra et al, 2007;Pisal et al, 2007). Few studies have drawn samples from low income or rural communities (Bharat et al, 2001;Pallikadavath et al, 2005;Rogers, et al, 2006). In all the qualitative studies, with the exception of Bharat et al (2001), positive people are treated as a homogeneous group disregarding other identities they may have as sex worker or MSM.…”
Section: Methodology Of Hiv/aids Stigma Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative studies are based on samples ranging in size from 200 to 97 240 respondents from the student, general population (NACO, BSS-2006) and health staff (Mahendra et al, 2007;Pisal et al, 2007). Few studies have drawn samples from low income or rural communities (Bharat et al, 2001;Pallikadavath et al, 2005;Rogers, et al, 2006). In all the qualitative studies, with the exception of Bharat et al (2001), positive people are treated as a homogeneous group disregarding other identities they may have as sex worker or MSM.…”
Section: Methodology Of Hiv/aids Stigma Researchmentioning
confidence: 99%
“…Some of the earliest studies on AIDS in India were carried out in the 90s and a majority assessed knowledge about HIV/AIDS and attitudes towards HIV-infected people among the general public, mainly students (Ambati, Ambati & Rao, 1997;Lal, Vasan, Sarma, & Thankappan, 2000;Pramanik, Chartier & Koopman, 2006), adults in general population (Porter, 1993) or health providers, mainly nursing staff (Lal, Kumar, Ingle & Gulati,1998;Datta & Bandopadhyay,1997;Kermonde, Holmes, Langkham, Thomas & Gifford, 2005;Kumar, Lal, Ingle & Gulati, 1999;Kumar, Mohan, Seenu, Kumar, Nandi & Sarma, 2002), and more recently among pregnant women (Rogers, Meundi, Amma, Rao, Shetty, Antony et al, 2006;Rahbar, Garg, Tripathi, Gupta & Singh, 2007). The findings from these studies are fairly consistent with regard to attitudes towards PLHA.…”
Section: What Do Quantitative Studies Tell Us?mentioning
confidence: 99%
See 1 more Smart Citation
“…Acquired Immune Deficiency Syndrome (AIDS) epidemic knocks decades of countries national development and it can also devastate families and communities worldwide [1]. The rising prevalence of HIV among pregnant women in rural India is of great concern [2].In India; several thousand of HIV-infected babies are expected to be born every year [3]. India is now in the grip of so-called type 4 pattern of AIDS epidemic which shifts from high risk group to the bridge population (clients of sex workers, STD patients) and then to general population, as a whole [4].…”
Section: Introductionmentioning
confidence: 99%
“…A study of pregnant women in India showed that although the majority of women stated they were willing to be tested for HIV, they were also highly concerned about the reactions of their husbands, families, and community should it be found that they were seropositive. Additionally, not breastfeeding (recommended to prevent maternal-child HIV transmission) was widely believed to be a sign that a woman was a bad mother or had been unfaithful to her husband (Rogers et al, 2006). Women in particular are often reluctant to speak about genital health issues, one study cites "shyness" as the single biggest barrier in seeking STI treatment (Gibney et al, 1999).…”
Section: Cultural Barriersmentioning
confidence: 99%